Insurreição impressa: a instrumentalização da imprensa em episódios do movimento operário pernambucano (1900 a 1930). - Moura, Joel Rodrigues de (2023)
The main objective of the research was to capture the trajectory of the social group formed by the political labor movements in Pernambuco in the middle of the 19th century and the first decades of the 20th century.Emphasis was placed on the period from 1921 to 1922, a period in which the working-class newspaper “Diário do Povo – Organ of the Collective Interests of Pernambuco” was printed, one of the main sources of the study.The investigation of digital collections such as the library of the National Library, and physical collections such as the Municipal Library of Recife, the Public Archive of the State of Pernambuco and the Central Library of the Catholic University of Pernambuco was conducted, with a theoretical foundation based on the search for indexed articles and books.The research resulted in four distinct texts that together capture parts of a whole that was the Pernambuco labor movement at the dawn of the 20th century, which are freely available to the general public, in addition to fragments of publications from the journal digitized during the research.The main understanding achieved is that the workers' newspapers were a catalyzing tool for the mobilization and class and political organization of workers not only in Pernambuco, but throughout the country.Workers' newspapers appear as invaluable sources of information about these movements and present us with a window to understand the difficulties, struggles and achievements of this new social class, severely attacked by a capitalist society that announced itself to be modern, but at the same time still had both feet strongly rooted in the slave culture.